Between policy and practice: Project-based learning in Indonesian in-service English teachers’ professional education and classroom teaching - Suciwati, Ika; Ramli; Zuo, Jianing (Universitas Ahmad Dahlan, 2025)
Project-Based Learning (PBL) has been widely promoted as a learner-centred pedagogy in English Language Teaching (ELT) and is increasingly emphasized in teacher professional education programs. However, limited research has examined how in-service teachers experience learning PBL during professional education and how such learning is subsequently enacted in classroom practice, particularly in online professional development contexts in developing countries. Grounded in Vygotsky’s social constructivist theory, this exploratory qualitative study investigates Indonesian in-service English teachers’ experiences of PBL during their Teacher Professional Education (TPE) program and their enactment of PBL in secondary school classrooms. Data were collected through in-depth semi-structured interviews with three in-service English teachers and analyzed thematically. The study highlights a pedagogical disconnect between individualised professional learning experiences and socially mediated classroom practice and suggest that effective professional education for PBL requires structured opportunities for sustained collaboration, guided mediation, and technology-supported interaction that mirror the pedagogical principles teachers are expected to implement. This study contributes to international discussions on teacher professional learning, PBL enactment, and digitally mediated pedagogy in EFL contexts.